Mathematical Modelling of Coordinate Paraphase Photodetector Characteristics - V. B. Yarzhembitsky; A. I. Svistun; N. V. Yarzhembitskaya (Наука и техника)
The paper proposes a mathematical modelling of two-barrier structure photoresponse. The analysis of spectral and coordinate characteristics of paraphase photodetectors has been carried out depending on their parameters, illumination geometry and excitation conditions. It